O wartościowaniu dóbr ekonomicznych - Giza, Wojciech (Annales. Etyka w Życiu Gospodarczym, 2015)
The presented study includes an analysis of the category of ‘good’ on the basis of philosophy and economics. Particular attention was paid here to the factors determining the monetary value (price) of an economic good. While achieving the assumed objective of the research, answers to the following questions were sought: What is the difference, therefore, in the interpretation of good as an axiomatic category and good which the economy deals with? What is the basis for the valuation of goods which are the subject of economic analysis? While seeking answers to these questions, an attempt was made to justify the thesis according to which contemporary understanding of the way of valuating goods by the market is limited to accepting the price understood as a variable representing a kind of relationship set in a given time period.